Distribution of Bali Cattle Farmers and Break-Even Analysis: Case in Barru Regency South Sulawesi - Indrawirawan; Bambang Suwignyo; Tri Anggraeni Kusumastuti (ANIMAL PRODUCTION, 2023)
Barru Regency is an area of high indigenous Bali cattle population in South Sulawesi, Indonesia. The purpose of this study was to determine the economic analysis and mapping analysis of the location of smallholder Bali cattle farming. The research location is at Tanete Riaja District, Barru Regency, South Sulawesi. Purposive sampling was used to select 121 respondents, 75 from the breeding systems and 46 from the Bali cattle fattening systems. Observation and interviews are used to collect data. Data collection included the profiles of farmers, reproduction and production performance, and inputs and outputs of smallholder Bali cattle farming. Along with the interview, the location of farmers was recorded using a GPS receiver. The economic analysis used four criteria: Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP). The overlay method is used to map the farmers' locations. The results showed that the breeding system was feasible with the value of NPV of IDR 10,640,251, BCR of 1.30, IRR of 19.20%, and PP of 4.34 years. The fattening system was feasible with the value of NPV of IDR 34,569,548, BCR of 1.21, IRR of 36.91%, and PP of 2.64 years. Farmers' location maps showed that all farmers, both breeding and fattening, are located on low elevation land which is considered more suitable for Bali cattle farming because of good land fertility, suitable forage areas, and an abundant supply of food crops waste.